INNOVATIVE DEVELOPMENT OF AGRICULTURE IN THE CONDITIONS OF MODERNIZATION OF THE ECONOMY AND ITS SPECIFIC FEATURES - Sherkulovich, Altmishev Adil; Buriboevich, Japakov Norboy; Davlyatovich, Kurdashev Gudrat; Khamidovna, Abdujalilova Oygul; Ismatovich, Kholmatov Otabek; Abdulmanzurovich, Abdurakhmonov Ilkhomjon; Abdulazizovich , Abduvokhidov Akmal (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the sustainable development of agriculture and food security based on the innovative development of the agricultural sector as the most important sector of the national economy at the current stage of economic reform.